LEGAL REGULATION OF AGRICULTURAL COOPERATION IN THE REPUBLIC OF KAZAKHSTAN - Yerkinbayeva L.K. (Хабаршы. Заң сериясы, 2018)
This article discusses the theoretical and practical aspects of the legal status of agricultural cooperatives in Kazakhstan. Agriculture of the Republic of Kazakhstan is one of the main sectors of the economy. The study of the legal aspects of the activities of agricultural cooperatives will improve agricultural pro-duction and thus ensure the food security of the country. The author, determining the relevance of the article, indicates the place and importance of agricultural cooperatives in the legislation of the Republic of Kazakhstan. Critically discussing the views of scientists from the point of view of the legal definition of agricultural cooperatives, the author’s reference is presented. There are also proposals to improve the current legislation in this area. As a result of the study, the author, presenting the basic principles of agricultural cooperatives, points to the role of effective application of the principles in improving the legislation of agricultural cooperatives.